Do physicians preach what they practice? A study of physicians' health habits and counseling practices - Wells, K B; Lewis, C E; Leake, B; Ware, Jr, J E (JAMA : the journal of the American Medical Association, 1984)
We examined the relation of physicians' clinical specialty, personal health habits, and health-related beliefs to their practices in counseling about smoking, weight, exercise, and alcohol. We surveyed a random sample of members of a county medical society in selected specialties. Physicians with better personal health habits and more positive attitudes toward counseling counsel a broader range of patients and counsel more aggressively. Surgeons counsel less than nonsurgeons, even after controlling for differences in health-related attitudes and personal habits.